Knowledge and Breast Self-Examination Practice Among Health and Non-Health University Students - M Badzlul Rahmansyah; Farhan Aqil Putra Hermawan; Nurhidayati Nurhidayati; Rizka Vidya Lestari; Hanan Afifah (Dian Nuswantoro Semarang, 2026)
Breast cancer remains the most prevalent malignancy in Mataram City, with many cases diagnosed at advanced stages due to inadequate early screening. This study aims to analyze the relationship between breast cancer knowledge and Breast Self-Examination (BSE/SADARI) practice among health and non-health university students in Mataram. An observational analytic quantitative design with a cross-sectional approach was utilized. Data were collected from 256 female students across multiple universities in Mataram using a validated questionnaire distributed via Google Forms, selected through quota sampling. Data analysis included univariate descriptive statistics, Chi-Square tests, and Independent Sample T-tests. The results revealed that 41.4% of respondents had poor knowledge, while 56.3% demonstrated poor BSE practices. Bivariate analysis showed a statistically significant positive relationship between knowledge levels and BSE practice (), although the correlation strength was relatively weak. Students in the health cluster demonstrated significantly higher scores in both knowledge and practice compared to those in the non-health cluster (). This study concludes that while knowledge serves as a foundational requirement, a prominent